A Service Chain Discovery and Recommendation Scheme Using Complex Network Theory - Liu, Guoqi; Zhao, Yuli; Wang, Zhuang; Liu, Ying (Mathematical problems in engineering, 2014)
Service chain discovery and recommendation are significant in services composition. A complex network module based algorithm using services invocable relations is proposed to search useful service chains on the network. Furthermore, a new scheme for discovering composite services processes automatically and recommending service chains by ranking their QoS is provided. Simulations are carried out and the results indicate that some useful service chains in the dataset provided by the WSC2009 can be found by the new algorithm.